Electrical characteristics of pacing different portions of the His bundle in bradycardia patients. (28th December 2020) - Hu, Yiran; Gu, Min; Hua, Wei; Niu, Hongxia; Li, Hui; Chen, Xuhua; Zhang, Nixiao; Liu, Xi; Zhang, Shu
Abstract: Aims: His-bundle pacing (HBP) can be achieved in either atrial-side HBP (aHBP) or ventricular-side HBP (vHBP). The study compared the pacing parameters and electrophysiological characteristics between aHBP and vHBP in bradycardia patients. Methods and results: Fifty patients undergoing HBP implantation assisted by visualization of the tricuspid valvular annulus (TVA) were enrolled. The HBP lead position was identified by TVA angiography. Twenty-five patients were assigned to undergo aHBP and compared with 25 patients who underwent vHBP primarily in a prospective and randomized fashion. Pacing parameters and echocardiography were routinely assessed at implant and 3-month follow-up. His-bundle pacing was successfully performed in 45 patients (90% success rate with 44.4% aHBP and 55.6% vHBP). The capture threshold was lower in vHBP than aHBP at implant (vHBP: 1.1 ± 0.5 vs. aHBP: 1.4 ± 0.4 V/1.0 ms, P = 0.014) and 3-month follow-up (vHBP: 0.8 ± 0.4 vs. aHBP: 1.7 ± 0.8 V/0.4 ms, P < 0.001). The R-wave amplitude was higher in vHBP than in aHBP at implant (vHBP: 4.5 ± 1.4 vs. aHBP: 2.0 ± 0.8 mV, P < 0.001) and at 3-month follow-up (vHBP: 4.4 ± 1.5 vs. aHBP: 1.8 ± 0.7 mV, P < 0.001). No procedure-related complications and aggravation of tricuspid valve regurgitation were observed in most patients and echocardiographic assessment of cardiac function remained in the normal range in all patients during the follow-up. Conclusion: This study demonstrates that vHBP features a low and stable pacing capture threshold and high R-wave amplitude, suggesting better pacing mode management and battery longevity can be achieved by HBP in the ventricular side.